The suspended neighbourhood. Adret Pont-Rouge a projection between cartography and Facebook - Gamba, Fiorenza; Cattacin, Sandro (E|C, 2021)
What transforms a space into a place is, first, the possibility to be recognized as a landscape and to be inhabited and transformed by human agency. But what happens when the place must be created and its possibility to be inhabited strongly prejudiced? Is the medial projection able of representing the imaginary of this suspended district? This is the case of the newly constituted Adret Pont-Rouge neighbourhood in Geneva, which we analyze in this paper. A suspended neighbourhood, where the imaginaries of planners, the narrative of the association of future inhabitants and the expectations of inhabitants are unable to create the common identity of a place without history. A district where the hybridization between physical and digital space is at present still problematic.